Impact of adaptive gastric electrical stimulation on weight, food intake, and food intake rate in dogs. Issue 6 (30th December 2021) - Debelle, Adrien; Hesta, Myriam; de Rooster, Hilde; Bianchini, Erika; Vanhoestenberghe, Anne; Stock, Emmelie; Vanderperren, Katrien; Polis, Ingeborgh; Smets, Hugo; Cury, Joaquin; Acuña, Vicente; Delchambre, Alain; et al.
Abstract: Background: Gastric electrical stimulation (GES) has been studied for decades as a promising treatment for obesity. Stimulation pulses with fixed amplitude and pulse width are usually applied, but these have limitations with regard to overcoming habituation to GES and inter‐subject variation. This study aims to analyze the efficacy of an adaptive GES protocol for reducing food intake and maintaining lean weight in dogs. Methods: Six beagle dogs were implanted with a remotely programmable gastric stimulator. An adaptive protocol was designed to increase the stimulation energy proportionally to the excess of food consumption, with respect to the dogs' maintenance energy requirements. After surgery and habituation to experimental conditions, the dogs went through both a control and a stimulation period of 4 weeks each, in a randomized order. The stimulation parameters were adapted daily. Body weight, food intake, food intake rate, and postprandial cutaneous electrogastrograms (EGG) were recorded to assess the effect of adaptive GES. Results: Adaptive GES decreased food intake and food intake rate ( p < 0.05) resulting in weight maintenance. In the absence of GES, the dogs gained weight ( p < 0.05). Postprandial EGG dominant frequency was accelerated by GES ( p < 0.05). The strategy of adapting the stimulation energy was effective in causing significant mid‐term changes. Conclusion: Adaptive GES is effective for reducing food intake and maintaining lean weight. The proposed adaptive strategy may offer benefits to counter habituation and adapt to inter‐subject variation in clinical use of GES for obesity. Abstract : Using an adaptive gastric electrical stimulation protocol which increases the stimulation energy proportionally to the excess of food intake in dogs, we obtained: ‐ A significant decrease of food intake with respect to baseline (−42% by week 4). ‐ A significant decrease of food intake rate during the STIM period compared to the SHAM (−60% at week 4). ‐ A significant increase of the postprandial frequency of the gastric slow waves (+11% STIM vs. SHAM), as measured with a noninvasive cutaneous system.